Andragogical bases of professional handicraft teachers’ development in postgraduate teacher training - Ковальчук, Ірина Михайлівна (Pedagogy of Higher and Secondary Education, 2017)
The author reveals the relevance of the professional development of handicraft teachers in postgraduate teacher education, which is underpinned by strengthening of the world dynamics, the necessity of new technologies, services, and consequently, urgent need of professionalism. The problem of adult education and its theoretical aspects is revealed in the works of S. Vershlovskii T. Hromkova O. Gury, I. Drach, A. Dubaseniuk, S. Zmeiev, I. Ziaziun, A. Kukuiev, L. Lukianov, N. Nychkalo M. Knowles, S. Sysoiev and others.The aim of the article is to define andragogical principles that constitute a basis for building educational process and have positive impact on the professional development of handicraft teachers. For this purpose such methods are used as: system analysis and synthesis, comparison, generalization, systematization, study of scientific psychological, educational, methodical literature.The author considers the main characteristics of an adult, determines and justifies a system of andragogical principles of educational process building. In the author’s opinion andragogical principles include the principle of consistency and hierarchy, the principle of self-determination, the principle of subsidiarity, the principle of continuity, the scientific principle, the principle of innovation, interaction principle, the principle of stimulating development and self-activityorientation principle, the principle of analysis of professional experience and training. The foregoing andragogical principles are the foundation for an effective educational system and handicraft teachers professional development.The andragogical set of principles considered in the article is aimed at: changes in teaching students, in faculty training activities and formation of motivational and reflexive environment; improving of election methods of construction aggregate interaction of educational process; promotion of humanization ideas, democratization, personal and pedagogical activityorientation process; self-actualization of professional teachers technologies in conditions of constant changes in modern cultural and technological environment.